Identification of a novel immune-inflammatory signature of COVID-19 infections, and evaluation of pharmacokinetics and therapeutic potential of RXn-02, a novel small-molecule derivative of quinolone. (September 2022) - Lawal, Bashir; Kuo, Yu-Cheng; Rachmawati Sumitra, Maryam; Wu, Alexander T.H.; Huang, Hsu-Shan
Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic and respiratory infection that has enormous damage to human lives and economies. It is caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), a non-pair-stranded positive-sense RNA virus. With increasing global threats and few therapeutic options, the discovery of new potential drug targets and the development of new therapy candidates against COVID-19 are urgently needed. Based on these premises, we conducted an analysis of transcriptomic datasets from SARS-CoV-2-infected patients and identified several SARS-CoV-2 infection signatures, among which TNFRSF5/PTPRC/IDO1/MKI67 appeared to be the most pertinent signature. Subsequent integrated bioinformatics analysis identified the signature as an important immunomodulatory and inflammatory signature of SARS-CoV-2 infection. It was suggested that this gene signature mediates the interplay of immune and immunosuppressive cells leading to infiltration-exclusion of effector memory T cells in the lungs, which is of translation relevance for developing novel SARS-CoV-2 drug and vaccine candidates. Consequently, we designed and synthesized a novel small-molecule quinoline derivative (RXn-02) and evaluated its pharmacokinetics in rats, revealing a peak plasma concentration (Cmax) and time to Cmax (Tmax) of 1.756 μg/mL and 0.6 h, respectively. Values of the area under the curve (AUC) (0–24 h) and AUC (0 h∼∞) were 18.90 and 71.20 μg h/mL, respectively. Drug absorption from the various regional segments revealed that the duodenum (49.84%), jejunum (47.885%), cecum (1.82%), and ileum (0.32%) were prime sites of RXn-02 absorption. No absorption was detected from the stomach, and the least was from the colon (0.19%). Interestingly, RXn-02 exhibited in vitro antiproliferative activities against hub gene hyper-expressing cell lines; A549 (IC50  = 48.1 μM), K-562 (IC50  = 100 μM), and MCF7 (IC50  = 0.047 μM) and against five cell lines originating from human lungs (IC50 range of 33.2–69.5 μM). In addition, RXn-02 exhibited high binding efficacies for targeting the TNFRSF5/PTPRC/IDO1/MK signature with binding affinities (ΔG) of −6.6, −6.0, −9.9, −6.9 kcal/mol respectively. In conclusion, our study identified a novel signature of SARS-CoV-2 pathogenesis. RXn-02 is a drug-like candidate with good in vivo pharmacokinetics and hence possesses great translational relevance worthy of further preclinical and clinical investigations for treating SARS-CoV-2 infections. Graphical abstract: Image 1 Highlights: Identification of novel gene signature of SARS-coV2 infection. The novel gene signature is associated with immune-inflammatory response of SARS-coV2 infection. The gene signature suggestively mediates the infiltration-exclusion of effector memory T cells in the lungs. RXn-02 demonstrated  in vitro  anti-proliferative properties against the SARS-coV2 gene signature hyper-expressing cell lines. RXn-02 has good drug-likeness, PK, and potential for targeting the SARS-coV2 gene signature.